Do particular design features assist people with aphasia to comprehend text? An exploratory study. Issue 3 (27th November 2015) - Wilson, Lucy; Read, Jennifer
Abstract: Background: Much of the evidence underlying guidelines for producing accessible information for people with aphasia focuses on client preference for particular design features. There is limited evidence regarding the effects of these features on comprehension. Aims: To examine the effects of specific design features on text comprehension. It was hypothesized that font style, letter case and supporting images would all have a significant impact on people with aphasias' ability to comprehend text. Methods & Procedures: Participants ( N = 9) read 35 paragraphs and selected the most appropriate word or phrase from a choice of four to finish the final sentence. Reading comprehension was assessed in three conditions: font style, letter case and text with a supporting image. One‐way analyses of variance (ANOVAs) with Bonferroni post‐hoc tests were used to test the effect of each design feature on reading comprehension. Outcomes & Results: People with aphasia comprehended significantly more written information when presented in sans‐serif font than in a serif style ( p = .01) and when presented in lower case than in upper case ( p = .03). The inclusion of a single supporting image to illustrate a paragraph of text did not have a significant effect on comprehension. Conclusions & Implications: This research supports the premise that font style and letter case have a significant effect on text comprehension, but that illustrating a paragraph of text with a single image may not significantly improve comprehension when text is written at a low readability level. Although it is critical to produce accessible information, improving comprehension is only one rationale for modified text presentation and therefore these results must be viewed in the context of other recommendations.